Day 2 Wed, October 30, 2019 2019
DOI: 10.4043/29818-ms
|View full text |Cite
|
Sign up to set email alerts
|

Using Wireline Logging and Thin Sections to Identify Igneous Contact Metamorphism and Hydrothermal Influence on Presalt Limestone Reservoirs in Libra Block, Santos Basin

Abstract: A methodology to confirm the direct contact metamorphism of intrusive rocks and related hydrothermal modification on presalt limestone reservoirs, in Libra Block of Santos Basin, is presented. The approach is based on systemic study of cores, sidewall cores, traditional wireline logging, ECS and NMR of boreholes. Type and characteristics of metamorphism in contact aureoles between intrusive bodies and limestones are confirmed. NMR was used to evaluate porosity change of limestone. Thin sections and ECS were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The occurrence of volcanoes, lava flows, and hydrothermal vents at various stratigraphic levels indicates that igneous activity was punctuated. Previous works describe three main magmatic events after rift initiation in Campos Basin: late Aptian (c. 112 -118 Ma), Santonian-Campanian (c. 70 -80 Ma) and Paleocene -Eocene (c. 40 -60 Ma) (Oreiro, 2006;Moreira et al, 2006;Winter et al, 2007;Thomaz Filho et al, 2008;Ren et al, 2019). Late Aptian magmatism is associated with the final breakup between the South American and African continents (Thomaz Filho et al, 2008).…”
Section: Timing Of Igneous Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of volcanoes, lava flows, and hydrothermal vents at various stratigraphic levels indicates that igneous activity was punctuated. Previous works describe three main magmatic events after rift initiation in Campos Basin: late Aptian (c. 112 -118 Ma), Santonian-Campanian (c. 70 -80 Ma) and Paleocene -Eocene (c. 40 -60 Ma) (Oreiro, 2006;Moreira et al, 2006;Winter et al, 2007;Thomaz Filho et al, 2008;Ren et al, 2019). Late Aptian magmatism is associated with the final breakup between the South American and African continents (Thomaz Filho et al, 2008).…”
Section: Timing Of Igneous Activitymentioning
confidence: 99%
“…Immediately after salt deposition (late Aptian, c. 116 -111 Ma), igneous extrusions and intrusions were emplaced during several magmatic pulses across southeast Brazil, from the late Upper Cretaceous to the Early Paleogene (Figure 2c), particularly during c. 60-40 Ma and c. 80-70 Ma (Figure 1b;Oreiro, 2006;Moreira et al, 2006;Thomaz Filho et al, 2008;Ren et al, 2019). By quantifying the percentage of volcanic fragments in different deep-water reservoirs of the Campos Basin, Fetter et al (2009) suggested that the climax of volcanism occurred in the Late Maastrichtian.…”
Section: Magmatism In Campos Basinmentioning
confidence: 99%
“…The authors described 10 hydrothermal vents, seven with dome-shaped geometries and 9 Please cite as https://doi.org/10.1016/j.jsames.2023.104314 three with eye-shaped geometries, all of which were associated with the two Early Cretaceous magmatic episodes (Figure 1b). Immediately after salt deposition (late Aptian, c. 116 -111 Ma), igneous extrusions and intrusions were emplaced during several magmatic pulses across southeast Brazil, from the late Upper Cretaceous to the Early Paleogene (Figure 2c), particularly during c. 60-40 Ma and c. 80-70 Ma (Figure 1b;Oreiro, 2006;Moreira et al, 2006;Thomaz Filho et al, 2008;Ren et al, 2019). By quantifying the percentage of volcanic fragments in different deep-water reservoirs of the Campos Basin, Fetter et al (2009) suggested that the climax of volcanism occurred in the Late Maastrichtian.…”
Section: Magmatism In Campos Basinmentioning
confidence: 99%
“…Basin: late Aptian (c. 112 -118 Ma), Santonian-Campanian (c. 70 -80 Ma) and Paleocene -Eocene (c. 40 -60 Ma) (Oreiro, 2006;Moreira et al, 2006;Winter et al, 2007;Thomaz Filho et al, 2008;Ren et al, 2019). Late Aptian magmatism is associated with the final breakup between the South American and African continents (Thomaz Filho et al, 2008).…”
Section: Timing Of Igneous Activitymentioning
confidence: 99%